PENDEKATAN MODEL MATEMATIS UNTUK MENENTUKAN PERSENTASE MARKUP HARGA JUAL PRODUK - Oviliani Yenty Yuliana; Yohan Wahyudi; Siana Halim (Institute of Research and Community Outreach - Petra Christian University, 2002)
The purpose of this research is to design Mathematical models that can determine the selling volume as an alternative to improve the markup percentage. Mathematical models was designed with double regression statistic. Selling volume is a function of markup, market condition, and substitute condition variables. The designed Mathematical model has fulfilled by the test of: error upon assumption, accurate model, validation model, and multi collinear problem. The Mathematical model has applied in application program with expectation that the application program can give: (1) alternative to decide percentage markup for user, (2) Illustration of gross profit estimation that will be achieve for selected percentage markup, (3) Illustration of estimation percentage of the units sold that will be achieve for selected percentage markup, and (4) Illustration of total net income before tax will get for specific period. Abstract in Bahasa Indonesia : Penelitian ini bertujuan untuk merancang model Matematis guna menetapkan volume penjualan, sebagai alternatif untuk menentukan persentase markup harga jual produk. Model Matematis dirancang menggunakan Statistik Regresi Berganda. Volume penjualan merupakan fungsi dari variabel markup, kondisi pasar, dan kondisi pengganti. Model Matematis yang dirancang sudah memenuhi uji: asumsi atas error, akurasi model, validasi model, dan masalah multikolinearitas. Rancangan model Matematis tersebut diterapkan dalam program aplikasi dengan harapan dapat memberi: (1) alternatif bagi pengguna mengenai berapa besar markup yang sebaiknya ditetapkan, (2) gambaran perkiraan laba kotor yang akan diperoleh setiap pemilihan markup, (3) gambaran perkiraan persentase unit yang terjual setiap pemilihan markup, dan (4) gambaran total laba kotor sebelum pajak yang dapat diperoleh pada periode yang bersangkutan. Kata kunci: model Matematis, aplikasi program, volume penjualan, markup, laba kotor.